PENGOLAHAN SAMPAH RUMAH TANGGA MENJADI PUPUK ORGANIK DAN PAVING BLOCK DI KECAMATAN DEMAK - Purwanto Purwanto; Ramli sangaji (Jurnal Universal Technic, 2022)
Garbage is a problem that has become a global environmental issue. Problems that arise in each region can vary, whether it is about the accumulation of organic or non-organic waste. One solution to this waste problem is the existence of waste processing activities. Waste processing is part of waste management by reducing the amount of waste, in addition to utilizing the values contained in the waste itself (recycled materials, other products, and energy). Waste management is crucial and important at this time, given the large volume of waste generated in each region and needs to be handled to keep the environment clean and nice. The waste problem in Semarang Regency, especially in the Demak District, is the chosen place in this study. Through the study of literature, followed by the related waste in each village in the exploration, by the development of solutions for each problem. Organic waste that can be processed into organic fertilizer, non-organic waste, especially plastic can be a advantogous material to produce paving blocks. The results of this research are also compiled in the form of an educative and interesting ebook to inspire the community and encourage positive activities for the community.